New Hope for Lasting 'Spree' Simon Tribute. - Joseph, Terry (Express)
A tribute to pan pioneer Winston ‘Spree’ Simon may become a reality twenty-five(25) years after his death. According to the spokesman for the Community Development Committee Horace Raymond, there is fresh hope for a commemorative stamp from TTPost.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Simon, Winston; Musicians -- Trinidad and Tobago